The Assessment of the Competitiveness of Adhesive Bandages Used in Peripheral Vascular Diseases in Geriatric Patients - Savinova, O V; Babaskin, D V; Krylova, O V; Udovichenko, E V; Winter, E A (Journal of pharmaceutical sciences and research, 2018)
The data found in the study on the impact and evaluation of research subjects allow identifying competitive advantages of different methods of the dressings' fixation on the wound, which will streamline the process of peripheral vascular diseases' therapy in elderly patients and the expenditure of material resources by the medical organization. The results of the assessment of the competitiveness of adhesive bandages to fix a bandage on the wound in geriatric patients with peripheral vascular diseases provide information for making managerial decisions in optimizing the management of a medical organization and increasing competitive advantages in the market of medical services. [...]there is an opportunity to evaluate the real competitiveness through the expert assessment and using the ranking method for calculating parametric indexes for a particular good or service and its competitors on the market. The results of the assessment of the competitiveness of adhesive bandages for fixation on the wound provide information for making managerial decisions when optimizing management of the clinic and increasing the competitive advantages in the market of medical services by saving the resources of the organization. 3.